Modern methods of surgical rehabilitation of patients adhesion deformation or absence of the conjunctival cavity in anophthalmos (Ukrainian Journal of Ophthalmology, 2026)
Modern methods of surgical rehabilitation of patients adhesion deformation or absence of the conjunctival cavity in anophthalmos